Predição do lucro por mudança unitária nos critérios de seleção de bovinos leiteiros no semi-árido do Nordeste - Ximenes, Luciano Jany Feijão (2009)
The economic values represent the profit per unit of improvement in the characteristics were calculated based on husbandry and accountancy records of a production system of dairy cattle crossbred Holstein x commercial farm located in the semiarid of the State of Ceará, Brazil. For these calculations we used two methods: 1) from the partial derivative of profit for each feature (RT - TOC) and 2) the partial derivative of the ratio RT / COT. In both methods the economic values were converted to equivalent-milk. For the first method, the economic values obtained were 0.68 / kg for milk, -9.14 / case of mastitis, 29.28 per kg of milk per minute for milk flow, -41.74 / services-conception , 3.67 / day of herdlife, -0.06 / day for age at first calving and -9.55 / kg body weight. The values of the second method were similar to the first probably because the ratio RT / COT have been close to 1 (1.06). The characteristics of the number of service / conception, mastitis, body weight, dry cow weight and age at first calving had negative economic values, milk flow, milk yield and herdlife showed genetic profit in the system. Therefore, all these characteristics should be included in the economic objective of selection for dairy cattle on farms that have management and creating conditions similar to that evaluated in this study.